Financial Management behavior among Malaysian SME owners: some new insights from a qualitative study / Shukriah Saad … [et al.] - Saad, Shukriah; Ismail, Aida Hazlin; Mat Dangi, Mohamad Ridhuan; Zainal Abidin, Adnan; Hashim, Muhamad Ridzuan (Faculty of Accountancy, 2019)
Small and medium-sized enterprises (SMEs) make the major contribution to the economic growth and employment in Malaysia. Although SMEs role in the economy is substantial, however many of the companies are affected by financial management problems. Given that financial management is one of the key aspects of the wellbeing and survival of a business, hence the owner of the SMEs need to be concern on their firm’s financial resources. In terms of financing, SMEs can seek from various types of financial institutions, including banking institutions, development financial institutions, leasing and factoring companies as well as venture capital companies. In addition, SMEs can also make use of various specific purpose special funds set up by the Government to help SMEs. Despite various financing extended to SMEs, past studies found that the inaccessibility to finance is listed as one of the primary external constraints faced by SMEs. Nevertheless, recognizing the financing alone is not sufficient, the initiatives on financing should be used with proper records and future plans. Thus, knowledge in financial management is became very important. One of the key elements for SMEs to continue improving their performance with a dynamic market in Malaysia is to practice prudent financial management. It will ensure that all the available business resources are used efficiently and effectively to provide optimum return. Therefore, the aim of this study to identify the awareness and financial management practices/techniques/methods among the SMEs owner’s in urban and sub-urban area in Selangor. In addition, the factors that may influence the SME owner’s in making financial management decision will be examined in this study. Findings from this study may be useful to the government and financial providers to know the importance of educating the financial management knowledge among SMEs owners as well and the adoption of appropriate financial management tools among Malaysia SMEs.